Response of Plane Tree (Platanus orientalis L.) toward Environmental Pollution of Erbil City - Ismail T. Ahmed; Halmat A. Sabr (Zanco Journal of Pure and Applied Sciences, 2020)
The objective of the present study was to evaluate the leaves of plane tree (Platanus orientalis L.) impaired by traffic pollution. Trees from four locations of Erbil City were investigated. Leaf morphology, leaf and soil heavy metal concentration and leaf pigments were measured from the collected leave samples. One way ANOVA was used to compare means and determine significant variation among the studied parameters. The highest increase in chlorophyll a and total chlorophyll were obtained in Sami Abul-Rahman Park whereas, the highest reduction was observed in Ainkawa road. Likewise in case of carotenoid contents, non significant effect was obtained from samples. The study obviously points out that the motor vehicles stimulate air pollution may result in decreases the concentration of photosynthetic pigments in the plane trees exposed to road side air pollution. It is shown that the lowest metal concentrations were detected in Sami Abul-Rahman Park in comparing with the other locations. It is shown that the lowest metal concentrations such as Ni, Zn, Mn and Fe in soil and plant samples were detected in Gulan Street When compared with the other locations. According to the geoaccumulation index (Igeo), the soils were classified into uncontaminated and uncontaminated to moderately contaminate.